2017
DOI: 10.1177/2047487317711334
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk factors in relation to other cardiovascular risk factors in coronary heart disease: Results from the EUROASPIRE IV survey. A registry from the European Society of Cardiology

Abstract: Background Depression and anxiety are established psychosocial risk factors for coronary heart disease. Contemporary data on their prevalence and associations with other risk factors were evaluated as part of the EUROASPIRE IV survey. Design The design of this study was cross-sectional. Methods The study group consisted of 7589 patients from 24 European countries examined at a median of 1.4 years after hospitalisation due to coronary heart disease events. Depression and anxiety were assessed using the Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
3
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 38 publications
5
87
3
7
Order By: Relevance
“…20 Psychosocial. The EUROASPIRE IV survey 21 confirmed the high prevalence of symptoms of depression and anxiety in patients with CAD (22.4% and 26.3%, respectively). Both symptoms were more prevalent in women than men (30.6% vs. 19.8% and 39.4% vs. 22.1%, respectively), and were associated with lower educational level and a more sedentary lifestyle.…”
Section: Other Risk Markersmentioning
confidence: 80%
“…20 Psychosocial. The EUROASPIRE IV survey 21 confirmed the high prevalence of symptoms of depression and anxiety in patients with CAD (22.4% and 26.3%, respectively). Both symptoms were more prevalent in women than men (30.6% vs. 19.8% and 39.4% vs. 22.1%, respectively), and were associated with lower educational level and a more sedentary lifestyle.…”
Section: Other Risk Markersmentioning
confidence: 80%
“…57 Presence of anxiety and depression after a cardiac event was strongly associated with an unhealthy lifestyle and poor compliance with medications and risk factor modification. 89 Similarly, analysis of risk factors in the INTER-HEART study (n=29 972) revealed that psychosocial stress was twice as common in women and a more significant predictor of risk of future MI (OR, 3.49 versus 2.58 in men). 9,17 Interventions that enhance perceived social support, psychosocial factors, and emotional state by reassurance, support groups, stress-reduction intervention programs, health coaches, church support, and psychotropic medications might result in improved clinical outcomes.…”
Section: Recognition Of Other Important Determinants Of Healthmentioning
confidence: 97%
“…Using a representative sample of 10 012 permanent residents of Kraków, Poland, included in the HAPIEE study (Health, Alcohol and Psychosocial Factors in Eastern Europe), Kozela et found not only that lower levels of education and greater geographical deprivation were associated with higher risks of incident CVD in women, but also that associations for education were found within every level of deprivation, and associations for deprivation were found within every level of education. 7 Previous research also identified an impact of interactions between sex, depression, and lower level of education on CVD risk factors, 4 as well as of interactions between sex and depression on CVD outcomes. 8,9 More generally, Kozela et al 5 also replicate the INTER-HEART findings, which demonstrated that severe financial stress was associated with 33% increased odds for acute myocardial infarction.…”
Section: The Million Women Study In the United Kingdommentioning
confidence: 98%
“…1,2 An important step towards improved CVD prevention strategies is recognizing that psychosocial risk factors do not function independently or occur in isolation, but rather, they cluster together within individuals or groups. 4 This line of thought has traditionally been sorely lacking in empirical support specific to CVD, with the recognition of psychosocial risk -factor clustering largely based on narrative review papers. The study by Kozela et al 5 in this issue of Kardiologia Polska (Kardiol Pol) provides an important longitudinal perspective on the cumulative effects of clustered risk factors such as low level of education, material deprivation, low perceived control, and depressive symptoms in relation to incident CVD.…”
Section: The Million Women Study In the United Kingdommentioning
confidence: 99%